Exploring the relationship between United States governmental secrecy and democracy: Classification, cultures of secrecy, and the public sphere. - Hall, Harry Thomas, Jr. (My University, 2005)
For the past 60 years government secrecy in the form of officially classified documents has increased dramatically. According to the Information Security Oversight Office there were slightly fewer than 16 million classification decisions in 2004 alone. In what way does classification impact representative democracy as it is practiced in the United States? This dissertation employed hermeneutic analysis to investigate the phenomenon of government secrecy and its effects on democracy. Through the analysis of executive orders, legislation, and official documents, the nature and scope of government secrecy was explored. The internal effects of secrecy on the information flow between governmental agencies were investigated, as well as the external effects of secrecy between the government and its constituents. Findings suggest that overclassification not only negatively impacts the internal communication networks of the government, but also, negatively impacts the public sphere, as citizens are denied access to information vital to informed decision making. The effect of secrecy on civil liberties is also examined. What emerges from this comprehensive hermeneutic analysis is a simple pattern consisting of a threat, followed by increased secrecy and legislation, which finally results in the infringement on individual and group civil liberty. Historically, this pattern frequently repeats itself.
Keywords: Government information United States.; Sociology, General.; Freedom of information United States.; Speech Communication.; Official secrets United States.; Executive privilege (Government information) United States.; Political Science, General.; Security classification (Government documents) United States.